solve the question seen in the attachment
are yar dedo please ☹☹☹☹☹☹☹☹☹☹☹☹☹☹☹☹☹☹☹☹☹☹☹☹☹☹☹☹
![](https://hi-static.z-dn.net/files/dff/68affcb235af7fdef2a672dc3c703d0d.jpg)
Answers
Solution :-
SSS congruence rule = side - side - side
- if all three sides of two triangles are equal to each other, then the traingles are congruent by SSS congruency rule
CPCT : Corresponding parts of congruent triangles
- two or more triangles are congruent, then all of their corresponding angles and sides are congruent as well
__________________________
(i) prove that ∆ABM ≅ ∆ACM
in ∆ABM and ∆ACM
- AB = AC (given)
- BM = CM (given)
- AM = AM (common)
so, ∆ABM ≅ ∆ACM by SSS congruency rule
_______________________
(ii) find ∠CAM
we have, ∆ABM ≅ ∆ACM
➪ ∠CAM =∠BAM (by CPCT)
_______________________
(iii) find ∠ABM
we have, ∆ABM ≅ ∆ACM
➪ ∠ABM =∠ACM (by CPCT)
________________________
(iv) Find ∠AMC
now, in ∆AMC
★ by using angles sum property of a triangle
- sum of all interior angles of a triangle is equal to 180°
![](https://hi-static.z-dn.net/files/d69/a1e67ba90c76a95bd4e576a261c66751.jpg)
Answer:
SSS congruence rule = side - side - side
if all three sides of two triangles are equal to each other, then the traingles are congruent by SSS congruency rule
CPCT : Corresponding parts of congruent triangles
two or more triangles are congruent, then all of their corresponding angles and sides are congruent as well
__________________________
(i) prove that ∆ABM ≅ ∆ACM
in ∆ABM and ∆ACM
AB = AC (given)
BM = CM (given)
AM = AM (common)
so, ∆ABM ≅ ∆ACM by SSS congruency rule
_______________________
(ii) find ∠CAM
we have, ∆ABM ≅ ∆ACM
➪ ∠CAM =∠BAM (by CPCT)
\bold{: \implies \boxed{ \orange{\bold{∠CAM = 25 \degree}}}}:⟹
∠CAM=25°
_______________________
(iii) find ∠ABM
we have, ∆ABM ≅ ∆ACM
➪ ∠ABM =∠ACM (by CPCT)
: \implies \boxed{ \orange{\bold{∠ABM = 65 \degree }}}:⟹
∠ABM=65°
________________________
(iv) Find ∠AMC
now, in ∆AMC
★ by using angles sum property of a triangle
sum of all interior angles of a triangle is equal to 180°
\begin{gathered} \bold{ : \implies ∠CAM + ∠ACM + ∠AMC = 180 \degree } \\ \\ \bold{: \implies25 \degree + 65 \degree +∠AMC = 180 \degree } \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \\ \\ \bold{: \implies 90 \degree +∠AMC = 180 \degree } \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \\ \\ \bold{: \implies ∠AMC = 180 \degree - 90 \degree } \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \\ \\ \bold{: \implies \boxed{ \orange{ \bold{∠AMC = 90 \degree}}} }\: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \end{gathered}
:⟹∠CAM+∠ACM+∠AMC=180°
:⟹25°+65°+∠AMC=180°
:⟹90°+∠AMC=180°
:⟹∠AMC=180°−90°
:⟹
∠AMC=90°